2019
DOI: 10.5588/pha.18.0055
|View full text |Cite
|
Sign up to set email alerts
|

Stigma against tuberculosis may hinder non-household contact investigation: a qualitative study in Thailand

Abstract: The study is a part of the research project entitled, 'Development of an operations manual and tools for enhancing the coverage of TB contact investigations and reducing their social burden and stigma', funded

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 25 publications
3
22
0
Order By: Relevance
“…As explored in the qualitative study, the other potential reasons for low rate of PTBP detection are hesitancy to disclose the details of TB symptoms due to stigma and distrust about TAs. Some other studies also revealed similar findings [27,28].…”
Section: Discussionsupporting
confidence: 74%
“…As explored in the qualitative study, the other potential reasons for low rate of PTBP detection are hesitancy to disclose the details of TB symptoms due to stigma and distrust about TAs. Some other studies also revealed similar findings [27,28].…”
Section: Discussionsupporting
confidence: 74%
“…The prevalence of stigma associated with TB has been shown to vary from 27% to as high as 82% in different settings across the world [ 10 13 ]. It was also found to be associated with nonadherence to treatment and treatment failure [ 14 ]; it hampers investigations of household contacts [ 15 ] and causes delay in case detection [ 16 ] and also associated with high mortality due to late presentation [ 17 ]. A study of the trend of TB case notification in Lagos state between 2011 and 2015 showed a decrease in the Case Notification Ratio from 82.9% in 2013 to 72.1% in 2015 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, including our previous study, 14 have reported that stigma against tuberculosis threatens contact investigation and the effort to end tuber-culosis because index patients keep their illness confidential and conceal information about their contacts. As a result, contacts at high risk of tuberculosis, such as children younger than 5 years of age do not benefit from tuberculosis prevention and care.…”
Section: Lessons Learntmentioning
confidence: 87%
“…The health system should improve health workers' communication and interview skills as these skills will improve the coverage of contacts and the yield of tuberculosis detection. 14,15 Some tuberculosis patients migrate for work to the capital city, Bangkok, but move to their hometown when they are sick. In this case, their contacts are in Bangkok and contact investigation should be performed by the local health service.…”
Section: Lessons Learntmentioning
confidence: 99%